New technologies for Natural Family Planning: the Brown Ovarian Hormone Monitor - Cappella, Anna Wanda; Saporosi, Aurora (Medicina e Morale, 1997)
During the last few years, various diagnostic techniques have been developed in the field of Natural Family Planning research, for instance, hormonal assays, the identification of particular substances present in the cervical mucus and the viscosity of the mucus itself, in order to find a simple and accurate fertility test which women can use by themselves. At present the Ovarian Monitor proposed by Brown is one of the most accurate techniques available for examining ovarian activity; it is able to recognise ovulation within a period of 12 hours and to demonstrate without a doubt when ovulation has occured. It can be applied successfully by couples who want to postpone a pregnancy and by those who would like to achieve one, in the desire to adhere to the Project of God for the conjugal union. Nevertheless any technical and diagnostic instrument identifying fertility should be considered a scientific support to Natural Method. In fact the use of technical instrument should be accompanied by the understanding and acceptance of the real meaning of Responsible Procreation. It is the teacher of the NM who transmits to the couple a "life style" of respect and care of the "other" person with the acceptance of fertility as a gift. In this way the teacher helps the couple to grow in love and generosity towards life.